Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\dfrac{\dfrac{x}{x-1}-\dfrac{x+1}{x}}{\dfrac{x}{x+1}-\dfrac{x-1}{x}}=\dfrac{\dfrac{x^2-\left(x^2-1\right)}{x\left(x-1\right)}}{\dfrac{x^2-\left(x^2-1\right)}{x\left(x+1\right)}}=\dfrac{\dfrac{1}{x\left(x-1\right)}}{\dfrac{1}{x\left(x+1\right)}}\)
\(\Leftrightarrow\left\{{}\begin{matrix}x\ne\left\{0;\pm1\right\}\\A=\dfrac{x+1}{x-1}\end{matrix}\right.\)
\(B=\frac{1+\frac{2}{x-1}}{1+\frac{2x}{x^2+1}}\)
\(B=\left(1+\frac{2}{x-1}\right):\left(1+\frac{2x}{x^2+1}\right)\)
\(=\left(\frac{x-1}{x-1}+\frac{2}{x-1}\right):\left(\frac{x^2+1}{x^2+1}+\frac{2x}{x^2+1}\right)\)
\(=\frac{x-1+2}{x-1}:\frac{x^2+1+2x}{x^2+1}\)
\(=\frac{x+1}{x-1}:\frac{\left(x+1\right)^2}{x^2+1}\)
\(=\frac{x+1}{x-1}.\frac{x^2+1}{\left(x+1\right)^2}\)
\(=\frac{x^2+1}{\left(x-1\right)\left(x+1\right)}\)
Chúc bạn học tốt !!!
a/ \(\frac{7x-14y}{x^2-4y^2}=\frac{7\left(x-2y\right)}{x^2-\left(2y\right)^2}=\frac{7\left(x-2y\right)}{\left(x-2y\right)\left(x+2y\right)}=\frac{7}{x+2y}.\)
b/ \(\frac{1-\frac{2y}{x}+\frac{y^2}{x^2}}{\frac{1}{x}-\frac{1}{y}}=\frac{\frac{x^2-2xy+y^2}{x^2}}{\frac{y-x}{xy}}=\frac{\left(x-y\right)^2}{x^2}.\frac{xy}{-\left(x-y\right)}=-\frac{y\left(x-y\right)}{x}=\frac{y\left(y-x\right)}{x}\)